FluLCVRT: Reflectance and fluorescence of leaf and canopy modeling based on Monte Carlo vector radiative transfer simulation. (September 2020) - Kallel, Abdelaziz
Highlights: Vector radiative transfer to model leaf-canopy fluorescence is proposed. Realistic 3-D mock-up leaf simulation is adapted. Fluorescence is created when radiation passes through chloroplasts. At level, databases of phase functions of scattering and fluorescence are created. At canopy, the leaf databases are used to propagate the radiation. Abstract: Chlorophyll fluorescence simulation is a hot topic in vegetation remote sensing as it allows to link measurements at leaf and canopy scales to the leaf photosynthetic activity. This work tries to simulate light propagation, scattering and fluorescence emission using 3-D vector radiative transfer theory that allows dealing with polarization. The model is called Fluorescence Leaf Canopy Vector Ratiative Transfer, FluLCVRT. Realistic 3-D mock-up of leaf is used to do simulation based on Monte Carlo ray tracing. Fluorescence is created when radiation passes through chloroplasts. The emission is proportional to the absorbed amount of radiation within the latter. Emitted fluorescence exits chloroplast in a random direction, therefore ray tracing is done separately for original radiation and fluorescence. Bidirectional reflectance, transmittance, and fluorescence are estimated at leaf level within a discrete tessellation for input and output angles, that are afterward saved as databases. Then at canopy level, ray tracing is done leaf by leaf, and at each iteration, original radiation is traced in addition to an auxiliary one relative to fluorescence. Both phenomena are governed by their leaf bidirectional distributions and the precalculated databases are used. Results at leaf level point out the variation of the bidirectional distributions. Particularly, reflectance and upward fluorescence are characterized by high specular effect and hot spot peak, respectively. Horizontally polarized radiation emits fluorescence less than the vertical one because its surface highly reflects radiation in the specular direction. Fluorescence in red and near-infrared increases and decreases with respect to chlorophyll content, respectively. Fluorescence is emitted from shallow chloroplasts in upward case. Meanwhile, in the downward one, it is mainly originated from shallow and deep chloroplasts in the red and near-infrared bands, respectively. At canopy level, the same chlorophyll, polarization, and bidirectional effects are observed except that hot spot peak becomes clear in reflectance. When LAI increases, fluorescence saturates at LAI equal 2 and 3 in red and near-infrared. Soil contribution in fluorescence is not too much since it does not diffuse an important amount of radiation in the chlorophyll absorption domain. A comparison between our model and Fluspect at leaf level shows differences in scattering and fluorescence. They are mainly due to the decrease of the chlorophyll efficiency in FluLCVRT due to the clumping of the chloroplasts within cell cytoplasm. Such an effect is not modeled in Fluspect.